If it's not what You are looking for type in the equation solver your own equation and let us solve it.
p+6=p+9
We move all terms to the left:
p+6-(p+9)=0
We get rid of parentheses
p-p-9+6=0
We add all the numbers together, and all the variables
-3!=0
There is no solution for this equation
| 94=3v+22 | | -5q+8=-10+4q | | 8k+23=95 | | -3(5-2x-6+4x=9 | | 3(4)+y=-1 | | -3/4x+15=3 | | 2y+5=40 | | 5/6b=79.50 | | h+1=6h+1-5h | | 23x=-30 | | -255=3d | | 17x+21+57=180 | | 5x+71=-14 | | {2}{3}x=-30 | | 5.x-70=216-8.x | | 3f-23=10 | | 9m+3=-5 | | −2(−3x+8)=6(x+4)−3 | | 2/3(9x-6)=9 | | -4t=116 | | -4x-7(-3x-6)=135 | | -6(5k+3)=-18-k | | 3/2(8x-4)-4(2x-3)=-10 | | 360=5x+91-2x | | 21x-2=x+8 | | -2.5x-5=9 | | 2x-12=15x-4x | | 12+-v=25 | | 53x+4=-25 | | 3f+(-7)=(-1) | | -x/3+4=-2 | | x/3=x/2-5/4 |